Tipologi, efektivitas dan elemen-Elemen utama dalam Kolaborasi Riset Internasional : Studi Kasus pada beberapa proyek riset Internasional di LIPI - Trina Fizzanty; Kusnandar Kusnandar; Wati Hermawati; Dini Oktaviyanti; Radot Manalu; Ishelina Rosaira Poerbosisworo (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2013)
This paper aims to present types as well as effectiveness in international research collaboration projects. Sixteen collaborative research projects at LIPI, an Indonesian government R&D institution, operated between 2001-2010 were evaluated. The effectiveness of the project was examined by comparing types and its benefits, and elements associated to the effectiveness of the projects. The research identified seven different types of collaboration and two major benefits which are publication and human resource or institutional capacity building. Meanwhile, a small number of the collaboration projects produced innovation, particularly where the triple helix structure - collaboration between academician, business and government - existed and promoted. Thus, three elements were found to beessential in supporting effective research collaboration: bargaining position; trust based competence; and trust based relationship.